Student perceptions, experiences and support within their current Bachelor of Nursing. (May 2019) - McNally, Stephen; Azzopardi, Toni; Hatcher, Deborah; O'Reilly, Rebecca; Keedle, Hazel
Abstract: Background: This study was developed to assist academics and curriculum designers to understand the perspectives and expectations of students when designing a program of study and inclusive of students as partners. The purpose of this qualitative study was to explore the perceptions and experiences of students enrolled in the Bachelor of Nursing (BN). Settings, participants, methods: The setting is a multi-campus university in Australia. Participants were currently enrolled and recruited from the Bachelor of Nursing, Bachelor of Nursing Advanced and Bachelor of Nursing Graduate Entry. Semi-structured focus group interviews and thematic analysis was used to collect and analyse the data. Results: Three major themes were identified from the focus group interviews: 1. Expectations; 2. Interesting and stimulating; and 3. Preparedness for study and clinical practice. Conclusion: Students held strong personal reasons for pursuing a nursing degree. The geographic location and international rankings were factors for choosing the university in this study. Student's perceptions and experiences of the curriculum and support identified that their BN program was interesting and adequately prepared them for clinical practice. Some areas for improvement were more detail during program orientation related to clinical practice requirements and more assistance with engaging with learning and teaching technologies.